Emotional Intelligence as a predictor of productivity and occupational stress of employees in electrical industries - Ogbuanya, Chinyere Theresa; Okeke, Chinedu I.; Maashin, Amenger (Universitas Negeri Padang, 2022)
The study investigated the relationship between emotional intelligence, occupational stress and productivity of employees in electrical industries. Research questions were answered while null hypotheses formulated were tested at 0.05 level of significance. The study adopted a correlational research design and was carried out in North Central States of Nigeria. The population for the study was 301 employees in electrical industries. The entire employees were involved in the study. The instrument for data collection was questionnaire titled Emotional Intelligence, Occupational Stress and Productivity Questionnaire (EIOSPQ). Five experts face- validated the instrument. The internal consistency of the questionnaire items was determined using Cronbach alpha reliability method and coefficients of 0.88 was obtained for Electrical Occupational Stress, 0.94 for Productivity of workers in electrical occupation, 0.85 for Emotional intelligence of employees. The overall reliability coefficient of the questionnaire was 0.96. Out of 301 copies of EIOSPQ administered, 295 copies were completed representing 98.01 percent return rate. Pearson product moment correlation and regression analysis were employed to analyse data for answering research questions and hypotheses. The findings on hypotheses revealed that: EI significantly predicts productivity of employees in electrical industries, EI does not significantly predicts occupational stress of employees in electrical industries, emotional intelligence was a significant moderator of the relationship between occupational stress and productivity of employees in electrical industries, demographic variables were not significantly influenced emotional intelligence and productivity of employees in electrical industries. It was recommended that employees in electrical industries should be sensitized through workshops and seminars on how EI can influence their productivity and occupational stress in their occupations.